2012
DOI: 10.5465/amj.2010.0270
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Team Diversity and Individual Team Member Creativity: A Cross-Level Interaction

Abstract: We theorized and tested the conditions under which cognitive team diversity is positively related to individual team member creativity. Hierarchical linear modeling results using 316 employees on 68 teams from Chinese companies indicated that a team member's creative self-efficacy moderated the relationship between cognitive team diversity and individual creativity: this relationship was positive only when creative self-efficacy was high. Further, "transformational leadership" moderated the relationship in suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
489
2
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(523 citation statements)
references
References 70 publications
10
489
2
22
Order By: Relevance
“…Chen et al, 2007;Kirkman, Chen, Farh, Chen, & Lowe, 2009;Shin, Kim, Lee, & Bian, 2012;Wang & Howell, 2012). Although theorists have long suggested that the group level factors may influence employee creativity (Drazin, Glynn, & Kazanjian, 1999;Woodman, Sawyer, & Griffin, 1993), research has yet to examine how transformational leadership at the group level influences the individual-level creative process engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2007;Kirkman, Chen, Farh, Chen, & Lowe, 2009;Shin, Kim, Lee, & Bian, 2012;Wang & Howell, 2012). Although theorists have long suggested that the group level factors may influence employee creativity (Drazin, Glynn, & Kazanjian, 1999;Woodman, Sawyer, & Griffin, 1993), research has yet to examine how transformational leadership at the group level influences the individual-level creative process engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Transformational leadership is understood to influence individuals' creativity through psychological empowerment [58]. This is enacted through a wide variety of mechanisms, including: encouraging individuals to take risks, thereby encouraging divergent thinking [56]; assuring individuals that their ideas are valued, thereby encouraging them to voice creative ideas [56]; and increasing motivation [59]. Shin et al [59] argue that "among the team contextual factors, leadership plays the dominant role in workplaces".…”
Section: 5mentioning
confidence: 99%
“…This is enacted through a wide variety of mechanisms, including: encouraging individuals to take risks, thereby encouraging divergent thinking [56]; assuring individuals that their ideas are valued, thereby encouraging them to voice creative ideas [56]; and increasing motivation [59]. Shin et al [59] argue that "among the team contextual factors, leadership plays the dominant role in workplaces". From the aforementioned, it is evident that leadership is understood to have an impact on the holistic understanding of the 'person' element (as it has been defined in this article), incorporating both the individual and the team or group in the organisational context.…”
Section: 5mentioning
confidence: 99%
“…Kreativitas didefinisikan sebagai produksi ide-ide baru dan berguna tentang produk, jasa, proses, dan prosedur oleh seorang karyawan (Shin, Kim, Lee, and Bian, 2012). Karya-wan yang memiliki ide-ide kreatif diharapkan mampu untuk menerapkan ide-ide tersebut dalam pekerjaannya, mengembangkannya, dan kemudian menyebarkan ide-ide tersebut kepada karyawan lain di dalam organisasi.…”
unclassified